Study of Inhibitory Effect of Honey on Various Pathogenic and Non-Pathogenic Microorganisms - Mistry, Richa; Shah, Gaurav (International Journal of Applied Sciences and Biotechnology, 2013)
Honey is a sweet food made by bees using nectar from flowers. The variety produced by honey bees (the genus Apis). The purpose of the present study was to determine in vitro antibacterial activities of different honey against various pathogenic and non-pathogenic organisms. Antibacterial activity of honey was determine by using well diffusion method in which different concentrations (20, 40, 60, 80, & 100 % v/v) of honey were used against various test pathogen. These organisms also tested against artificial honey for study of effect of sugar on its antibacterial activity. The results of these study was shown that wide range of variation in Zone of Inhibition (mm) of each type of honey and only very few organism inhibited due to effect of sugar. That shows there are also other components other than the sugar present in honey which ultimately responsible for antimicrobial activity. Due to obtaining maximum level of antibacterial activity of each honey it allow further investigation for treatment various infection and in curing of disease. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9179 Int J Appl Sci Biotechnol, Vol. 1(4): 279-281